Development of Fast Reverse Phase Liquid Chromatographic Method for Simultaneous Analysis of Betamethasone Dipropionate and Calcipotriol in Ointments and Bulk Drug - L. Turwale, Shankar; K. Dwivedi, Rajesh; T. Bachute, Madhusudan (Asian Journal of Chemistry, 2014)
A simple, fast and cost effective reverse phase isocratic liquid chromatographic method has been developed for the simultaneous analysis of betamethasone dipropionate and calcipotriol in ointment and bulk drugs. Mixture of water and methanol in the ratio of 200:800 v/v was used as mobile phase. Separation of drugs was achieved using C-18, 150 × 4.6 mm, 5 μ column from Phenomenox Luna. Analyses were carried out using UV detector at 265 nm wavelength and flow rate was kept 1 mL/min. The retention times were about 4.5 min for betamethasone dipropionate and about 6.9 min for calcipotriol. Linearity shows correlation coefficient r2 = 1 for calcipotriol and r2 = 0.999 for betamethasone dipropionate. The percentage recovery for betamethasone dipropionate and calcipotriol was 98.6 and 99.5 % respectively. Samples were subjected to alkali, acid, redox, thermal, humidity and photolytic degradation. Both the drugs were well separated from all degradants. Intra day (n = 6) and inter day precision (n = 12) gives RSD 0.67 and 0.63 %, respectively for betamethasone dipropionate and 1.14 and 0.88 %, respectively for calcipotriol. Method has been validated as per ICH guideline. Proposed method is simple and cost effective. Rapid separation of both the drugs is achieved within 7 min using simple mobile phase which makes this method simple, rapid and economic for routine simultaneous determination of calcipotriol and betamethasone dipropionate.